2010
DOI: 10.4149/av_2010_01_75
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNA-155 precursor in peripheral blood mononuclear cells from hepatitis C patients after antiviral treatment

Abstract: Chronic hepatitis caused by Hepatitis C virus (HCV) is the main source of liver cirrhosis, hepatocellular carcinoma, and extra-hepatic diseases. After treatment-induced resolution of hepatitis C, the persistence of HCV RNA in serum and peripheral blood mononuclear cells (PBMCs) is often observed. An expression of the precursor of microRNA-155 (miR-155) called BIC can be the factor responsible for a course of HCV infection. Therefore, we assessed the relationship between BIC expression and HCV RNA status in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 23 publications
(31 reference statements)
2
25
0
Order By: Relevance
“…Likewise, other studies have investigated miR-155 expression during hepatits C virus (HCV) infection, and a positive correlation was found between the posttreatment persistence of HCV RNA in the serum and peripheral blood mononuclear cells (PBMCs) of infected patients and the expression of the miR-155 precursor (BIC) in PBMCs (13). Another study has shown that HCV replication was positively correlated to the increased expression of mature miR-155 in PBMCs of HCV-infected patients (14).…”
Section: Introductionmentioning
confidence: 97%
“…Likewise, other studies have investigated miR-155 expression during hepatits C virus (HCV) infection, and a positive correlation was found between the posttreatment persistence of HCV RNA in the serum and peripheral blood mononuclear cells (PBMCs) of infected patients and the expression of the miR-155 precursor (BIC) in PBMCs (13). Another study has shown that HCV replication was positively correlated to the increased expression of mature miR-155 in PBMCs of HCV-infected patients (14).…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, the expression level of the primary precursor of miRNA-155 (BIC RNA), in the present study, demonstrated an upward tendency when the antigenomic HCV RNA strand was present in PBMCs. Our previous report showed that HCV RNA persistence in PBMCs observed after interferon treatment, was also accompanied by increased expression of pri-miR-155 (22). These findings suggest that miRNA-155 might be involved in regulation of HCV RNA synthesis in PBMCs, and as a potential factor of immunological response, may influence a course of the viral infection.…”
Section: Discussionmentioning
confidence: 93%
“…Blood samples were collected from 47 untreated, chronic hepatitis C patients (34 males, 13 females: ages [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] to identify the presence of HCV RNA in serum and genomic/ antigenomic HCV RNA strands in PBMCs. The study was accepted by the Bioethical Committee of the Medical University of Lodz (RNN/93/07/kB); blood samples were collected after informed consent had been obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Another piece of evidence about the relationship between miR-155 and HCV infection is that primiR-155 was found to be over-expressed in 100% of the PBMCs from patients in which HCV RNA persisted both in serum and peripheral blood mononuclear cells in spite of treatment with IFNa plus ribavirin. Pri-miR-155 was expressed in 83% of PBMCs from a group of patients without detectable HCV RNA only in serum, whereas the lowest expression, 67%, was found in patients without HCV RNA in both serum and PBMCs [26]. Over-expression of miR-155 was found to strengthen defenses against viruses by counteracting the immunosuppressive effect of IL-10 or TGF-b on TLR3-induced antiviral activity [27].…”
Section: Mir-155 and Hepatitis Virusesmentioning
confidence: 95%